2014
DOI: 10.1016/j.desal.2014.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Fenton coupled with nanofiltration for elimination of Bisphenol A

Abstract: 14 15Bisphenol A (BPA) is a typical Endocrine Disrupting Chemical (EDC), which is potentially 16 harmful during wastewater reclamation. In this study, its degradation during Fenton's process 17 under different operational conditions was investigated in combination with subsequent 18 nanofiltration of low concentration remnant BPA and compounds derived from oxidation. 19The results indicate that BPA could be degraded efficiently in aqueous phase by Fenton, even 20 at very low hydrogen peroxide doses. The treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Similarly, in the experiment by Bolong et al (2010), there was a significant decrease of BPA rejection from 60 to 30 % when the initial BPA concentration was increased from 100 to 500 ppm. Another study has also found that, during NF of BPA solutions, rejection is related to a size exclusion mechanism and the ability of the membrane to adsorb BPA (Escalona et al 2014). It has been suggested that physical adsorption on MF membranes is insignificant in pollutant removal because sorption is reversible and there is a limited active surface on the membrane with a limited number of sorption sites (Sun et al 2015).…”
Section: Bpa Removal By the Mf And Nfmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in the experiment by Bolong et al (2010), there was a significant decrease of BPA rejection from 60 to 30 % when the initial BPA concentration was increased from 100 to 500 ppm. Another study has also found that, during NF of BPA solutions, rejection is related to a size exclusion mechanism and the ability of the membrane to adsorb BPA (Escalona et al 2014). It has been suggested that physical adsorption on MF membranes is insignificant in pollutant removal because sorption is reversible and there is a limited active surface on the membrane with a limited number of sorption sites (Sun et al 2015).…”
Section: Bpa Removal By the Mf And Nfmentioning
confidence: 99%
“…These hybrid processes combine membrane filtration with BPA degradation during Fenton's process, among other techniques. However, significant membrane fouling was observed in the NF of the effluent even after Fenton oxidation (Escalona et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The principle of the process is the catalytic cycle of the reaction between ferrous ions (catalyst) and hydrogen peroxide (oxidant) to produce hydroxyl radicals ( Å OH) [16]. The hydroxyl radicals attack the organic compound leading to its partial or complete oxidation and producing carbon dioxide and water.…”
Section: Introductionmentioning
confidence: 99%
“…The removal of BPA was also investigated by a combined Fenton/nanofiltration process. Escalona et al [86] showed that BPA could be almost completely degraded by Fenton process, along with 78.2 and 59.1% conversions for COD and TOC, respectively. The subsequent nanofiltration of the Fenton treated effluent allowed a rejection of COD, TOC, colour and Fe 2+ always higher than 81%.…”
Section: Fenton-like Reactionmentioning
confidence: 99%